Synthesis of a Polyaniline Nanoparticle Using a Solution Plasma Process with an Ar Gas Bubble Channel - Shin, Jun-Goo (Polymers (Basel), 2019)
This work researched polymerization of liquid aniline monomer by solution plasma with a gas bubble channel and investigated characteristics of solution plasma and polyaniline (PANI). The injected gas bubble channel in the proposed solution plasma process (SPP) played a significant role in producing a stable discharge in liquid aniline monomer at a low voltage and furthermore enhancing the contact surface area between liquid aniline monomer and plasma, thereby achieving polymerization on the boundary of the liquid aniline monomer and plasma. Solution plasma properties were analyzed with voltage–current, optical emission spectroscopy, and high-speed camera. Conductivity, percentage yield, and firing voltage of PANI nanoparticle dispersed solution were measured. To investigate the characteristics of synthesized PANI nanoparticles, field emission scanning electron microscopy, dynamic light scattering, transmission electron microscopy, selective area electron diffraction (SAED) pattern, Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography, (1)H-nuclear magnetic resonance ((1)H-NMR), and X-ray photo spectroscopy (XPS) were examined. The FTIR, (1)H-NMR, and XPS analysis showed the PANI characteristic peaks with evidence that some quinoid and benzene rings were broken by the solution plasma process with a gas bubble channel. The results indicate that PANI nanoparticles have a spherical shape with a size between 25 and 35 nm. The SAED pattern shows the amorphous pattern.